PERAN BAWASLU DALAM MENINGKATKAN PARTISIPATIF MASYARAKAT PADA PENGAWASAN KAMPANYE PEMILU 2024 DI KOTA SUKABUMI - tuah nur; Damayanti, Mutia Siti; Amalia, Firda Dini; Rohmah, Siti (LPPM UNSAP & FISIP UNSAP, 2025)
In the context of the 2024 elections, Bawaslu is expeted to increase community participation in campaign supervision. This is important because high community participation can prevent fraudulent practices and violations that often occur in the campaign process. This study uses the role theory of Jim Ife and Frank Tesoriero (2014) with the dimensions of facilitation, educational role, technical role and representation role. The purpose of this study was to determine the role of Bawaslu increasing community participation in the supervision of the 2024 election campaign in Sukabumi City and to find out what obstacles Bawaslu faced in increasing community participation in the supervision of the 2024 campaign in Sukabumi City. In this study, the author used a descriptive qualitative approach to gain a comprehensive understanding of Bawaslu’s role in increasing community participation I the supervision of the 2024 Election Campaign in Sukabumi City. Based on the results of the research conducted, there is a need for further socialization that is more active and in-depth related in increasing community participation in election campaign supervision.